Pengaruh Penggunaan Media Pop Up Terhadap Hasil Belajar Siswa Kelas IV Pada Mata Pelajaran IPS di SD Inpres Napungbiri - Marianus Yufrinalis; Maria Disela Nogo (Peneliti.net, 2021)
This research is motivated by the lack of attention of students during learning. This can be seen from the number of students who do not pay attention to the teacher such as chatting in class or daydreaming. In addition, the social studies subject is considered a boring subject, so every time a teacher is given practice questions, students always find it difficult to answer them because they do not understand so that it has an impact on student learning outcomes. The research method used is quantitative research. This type of research is a type of experimental research. Based on the results of data analysis, it shows that the social studies learning outcomes on the pre-test score before being treated with an average value of 57.86 with the highest score of 93 and the lowest of 27. Meanwhile, the post-test score by giving treatment using pop-up media on learning outcomes has an average value. -Average of 74.66 with the highest score of 100 and the lowest 33. Judging from the pre-test and post-test scores for social studies cognitive learning outcomes, it can be seen that the average increase in learning outcomes on the post test (after treatment) is greater than what happened that happened in the pre test (before treatment). Student learning outcomes increased when treated using pop-up media on social studies learning outcomes.